2018
DOI: 10.5014/ajot.2018.024075
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Sensory Processing and Participation in Daily Occupations for Children With Autism Spectrum Disorder: A Systematic Review of Studies That Used Dunn’s Sensory Processing Framework

Abstract: Research measuring sensory processing in children with autism spectrum disorder (ASD) has shown variability in terms of measures used and participant ages, contributing to difficulty in interpreting and summarizing the findings of these studies. In an attempt to clarify the status of the literature, we conducted a systematic review of studies that focused on participation in daily occupations and evaluated sensory processing in children with ASD aged 5-13 yr using Dunn's sensory processing framework. Evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 26 publications
1
53
0
Order By: Relevance
“…The fact is that few clinical trials have shown positive effects of the sensory integration approach on reducing the sensory-related behaviors (Pfeiffer et al, 2011) or social functioning and self-care (Schaaf et al, 2014) in children with ASD. The systematic review of Hauer (2015), Case-Smith et al (2015), Weitlauf et al (2017), and Ismael et al (2018) showed a low or moderate effectiveness of sensory integration and sensory-based treatments on ASD even on the participation in activities of daily living that is the final goal of OT. When the therapists are trained and understand the impact of sensory approaches on experience, they are more likely to use these approaches (Thompson-Hodgetts & Magill-Evans, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The fact is that few clinical trials have shown positive effects of the sensory integration approach on reducing the sensory-related behaviors (Pfeiffer et al, 2011) or social functioning and self-care (Schaaf et al, 2014) in children with ASD. The systematic review of Hauer (2015), Case-Smith et al (2015), Weitlauf et al (2017), and Ismael et al (2018) showed a low or moderate effectiveness of sensory integration and sensory-based treatments on ASD even on the participation in activities of daily living that is the final goal of OT. When the therapists are trained and understand the impact of sensory approaches on experience, they are more likely to use these approaches (Thompson-Hodgetts & Magill-Evans, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of the sensory gym is to build their gross motor play and coordination. Meanwhile, it helps the children to improve their sensory functions reduce sensory over-stimulated concurrently due to the specially designed and unique equipment in the sensory gym (Ismael, Lawson, & Hartwell, 2018). Gross motor play is the primary sensory input for children with autism when occupying the sensory gym (Walker, 2015).…”
Section: Architecture Spaces Sensory Gymmentioning
confidence: 99%
“…* Note: Modified for dissertation formatting. The full table will be published in (Ismael, N., Mische Lawson, L., & Hartwell, J. (2016).…”
Section: Reynoldsmentioning
confidence: 99%
“…Besides learning more about the topic, I learned how to utilize the library resources, and how to collaborate with professionals in the library to complete this paper. This systematic review concluded that the evidence about the relationship between sensory processing and participation in ASD is limited and that more research is needed focusing on participation areas other than education and leisure (Ismael, Mische Lawson & Hartwell, 2016).…”
mentioning
confidence: 99%